The Importance of Parenting for a Generation of Well-Mannered Children: Empowering Parents Through Parenting Socialization - Jariyah, Ita Ainun; Adam, Jauhar Isbamami (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
Normative behavior is a behavior that is in accordance with the norms that surround them. Normative behavior is often interpreted as ethics, where an ethic is often also associated with morals. This article aims to outline the devotion of the importance of parenting to parents so that children's behavior does not deviate from existing morals and norms. Community service